Nonmesonic weak decay spectra of He-4(Lambda) - Bauer, E.; Galeao, Alfredo Pio Noronha Rodrigues [UNESP]; Hussein, M. S.; Krmpotic, F.; Parker, J. D. (Elsevier B.V., 2009)
To comprehend the recent Brookhaven National Laboratory experiment E788 on He-4(Lambda), we have outlined a simple theoretical framework. based on the independent-particle shell model, for the one-nucleon-induced nonmesonic weak decay spectra. Basically, the shapes of all the spectra are tailored by the kinematics of the corresponding phase space, depending very weakly on the dynamics, which is gauged here by the one-meson-exchange potential. In spite of the straightforwardness of the approach a good agreement with data is achieved. This might be an indication that the final-state-interactions and the two-nucleon induced processes are not very important in the decay of this hypernucleus. We have also found that the pi + K exchange potential with soft vertex-form-factor cutoffs (Lambda(pi) approximate to 0.7 GeV, Lambda(K) approximate to 0.9 GeV), is able to account simultaneously for the available experimental data related to Gamma(p) and Gamma(n) for H-4(Lambda), H-4(Lambda), and H-5(Lambda). (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Nonmesonic decay; One-nucleon spectra; Two-nucleon spectra; One-meson-exchange model; s-Shell hypernuclei; Independent-particle shell model